The Influence of Village Fund Towards Achievement of Society’s Welfare at Wukirsari Village, Yogyakarta - Septrida Kurniawati; Rayyan Ramdhani Djayusman; Ahmad Lukman Nugraha (Universitas Muhammadiyah Malang, 2018)
This paper aims to investigate the management of village fund in Wukirsari village and second, to analyze the influence of village fund towards the achievement of welfare of society in this village based on Mashlahah concept. The method used mixed method with Concurrent Triangulation model by combining equally between qualitative and quantitative method. The collecting data uses interview and questionnaire. the conclusion are; first, the management of village fund is established on annually program of development, while the implementation is managed by a teamwork of village development consists of government and society. All of development activities are completely controlled by the Head of Village and the Monitoring team. Second, the analysis shown that village fund has a positive influence toward welfare. The result of t test that analyzed by simple regression analysis concluded the value of village fund coefficient is 10,739 and t table is 1,661. It shows that tarithmetic > ttable (10,739 > 1,661). Coefficient determination value shows the result of adjusted R Square is 0.538 means that village fund variable (X) has 53,8% significance influence towards Mashlahah of society.